Overlapping Land Ownership Certificates - Muhammad Wildan Aulia Fahmi; Dian Latifiani (Indonesian Journal of Agrarian Law, 2027)
Land registration serves as the primary legal instrument for guaranteeing property rights security in Indonesia, yet the phenomenon of overlapping certificates of ownership (Sertipikat Hak Milik/SHM) continues to undermine the very legal certainty it is meant to provide. This study aims to analyze the legal consequences of overlapping certificates of ownership and to examine dispute resolution mechanisms under the Basic Agrarian Law (UUPA) No. 5 of 1960 and Government Regulation (PP) No. 24 of 1997 on Land Registration. This research employs a normative juridical method with a statutory approach (statute approach) and a conceptual approach (conceptual approach), utilizing primary and secondary legal materials gathered through library research and analyzed using descriptive-analytical techniques. The findings reveal that overlapping certificates generate three principal legal consequences: legal uncertainty over ownership status, potential certificate invalidation, and administrative liability of the National Land Agency. Dispute resolution may be pursued through non-litigation (mediation at the Land Office) or litigation before the General Court or Administrative Court, depending on the substance of the claim. Analysis confirms that the negative-tendency-positive publication system under UUPA operates in synchronization with the stronger evidentiary protection afforded by PP No. 24 of 1997, as the latter was enacted specifically to implement the former; overlapping certificates instead stem primarily from procedural and administrative weaknesses in land registration practice. This study concludes that resolving overlapping certificates requires strengthened procedural implementation, including clarification of the criteria for good faith and actual possession, digitalization of land administration, strengthened verification procedures, and institutional capacity building within BPN.